Islamic bank customer satisfaction, trust, loyalty and word of mouth : the CREATOR model - Sadia, Mehfooz Khan; Muhammad, Ali; Puah, Chin Hong; Hanudin, Amin; Muhammad Shujaat, Mubarik (Emerald Publishing Limited, 2023)
Purpose – This study aims to investigate two primary objectives. First, this study examines the influence of modified service quality dimensions on Islamic bank customer satisfaction using a compliance, reliability, empathy, assurance, tangible, operational efficiency, responsiveness (CREATOR) model. Second, the study explores the relationship between customer satisfaction, trust, loyalty and word of mouth (WOM) in Islamic banking of Pakistan. Design/methodology/approach – The proposed model was analyzed using PLS-SEM-based approach. A total of 312 usable responses were used for data analysis. Findings – The results indicate that all CREATOR dimensions have a significant positive impact on Islamic banks’ customer satisfaction. Similarly, this study also found a significant positive relationship between customer satisfaction, trust, loyalty and WOM. Overall, this study modified a well-established service quality framework by successfully implementing the CREATOR model in Islamic banking. Originality/value – This study will provide helpful policy guidelines for Islamic bank managers improve their service quality and strengthen their relationships with existing and new customers. The authors are also sure that their proposed model will add value to the ongoing service quality literature by indicating the role of operational effectiveness in increasing customer satisfaction and promoting positive WOM.